2020
DOI: 10.1053/j.gastro.2019.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Colitis and Risk of Inflammatory Bowel Disease in a Nationwide Cohort Study

Abstract: BACKGROUND & AIMS: Microscopic colitis shares pathogenetic mechanisms with inflammatory bowel disease (IBD). We studied the association between microscopic colitis and risk of incident IBD using data from a nationwide cohort study. METHODS: We conducted a prospective cohort study of all adults who received a diagnosis of microscopic colitis from 1990 through 2017 in Sweden and risk of incident IBD. Cases of microscopic colitis (n¼ 13,957) were identified through Systematized Nomenclature of Medicine codes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…Furthermore, a chronic active colitis pattern of injury does not necessarily indicate an IBD‐like course for patients with ICI colitis. A recent study has shown an increased risk for developing IBD in patients with microscopic colitis, 28 suggesting shared pathogenetic mechanisms that may explain the variety of morphological manifestations observed in ICI colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a chronic active colitis pattern of injury does not necessarily indicate an IBD‐like course for patients with ICI colitis. A recent study has shown an increased risk for developing IBD in patients with microscopic colitis, 28 suggesting shared pathogenetic mechanisms that may explain the variety of morphological manifestations observed in ICI colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of male in these individuals was 40.0%, which was significantly high in patients with I group (26.7%) compared to H group (Supplementary Table S4). Recent studies observed no evidence for associations between gastrointestinal inflammation and gender (Khalili et al, 2020). The median value of alanine aminotransferase and total bile acid was 18 U/L and 3.35 µmol/L, respectively.…”
Section: Study Populationsmentioning
confidence: 84%
“…34 We categorized educational level into compulsory school (≤9 years of education), upper secondary school (10-12 years), college or university (≥13 years), and a "missing" category for those missing education information. Three baseline comorbidities were also adjusted for: IBD due to its association with MC and PD risk 14,35 ; celiac disease as a risk factor for IBD and MC 13,36 ; and chronic obstructive pulmonary disease (COPD) as a proxy for long-term smoking, which is associated with both MC and PD risks. 2,13 The diagnoses of IBD and COPD were identified from the NPR using the Swedish ICD codes provided in Table S1.…”
Section: Adjustment For Confoundingmentioning
confidence: 99%
“…12,13 Recently, patients with MC were found to have substantially increased risk of classic inflammatory bowel disease (IBD) than individuals without MC, consistent with an earlier report on genetic overlap between the two diseases. 14,15 Interestingly, IBD has been associated with higher risk of PD, particularly when IBD developed in later adulthood (≥60 years). 16 Moreover, several physiological perturbations implicated in PD pathogenesis, such as autoimmune dysfunction, 17 intestinal dysbiosis, 18 and disruption of epithelial permeability, 19 are also demonstrated in MC, implying a possible connection between MC and PD.…”
mentioning
confidence: 99%